Proceedings. 31st Annual International Symposium on Computer Architecture, 2004.
DOI: 10.1109/isca.2004.1310768
|View full text |Cite
|
Sign up to set email alerts
|

TSOtool: a program for verifying memory systems using the memory consistency model

Abstract: In this paper, we describe TSOtool, a program to check the behavior of the memory subsystem in a shared memory multiprocessor. TSOtool runs pseudo-randomly generated programs with data races on a system compliant with the Total Store Order (TSO) memory consistency model; it then checks the results of the program against the formal TSO specification. Such analysis can expose subtle memory errors like data corruption, atomicity violation and illegal instruction ordering.While verifying TSO compliance completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 21 publications
1
73
0
Order By: Relevance
“…Their models treat memory reads and writes and barrier events, but lack register events and locked instructions with multiple events that happen atomically. Hangel et al [10] describe the Sun TSOtool, checking the observed behaviour of pseudo-randomly generated programs against a TSO model. Roy et al [17] describe an efficient algorithm for checking whether an execution lies within an approximation to a TSO model, used in Intel's Random Instruction Test (RIT) generator.…”
Section: Verified Checker and Resultsmentioning
confidence: 99%
“…Their models treat memory reads and writes and barrier events, but lack register events and locked instructions with multiple events that happen atomically. Hangel et al [10] describe the Sun TSOtool, checking the observed behaviour of pseudo-randomly generated programs against a TSO model. Roy et al [17] describe an efficient algorithm for checking whether an execution lies within an approximation to a TSO model, used in Intel's Random Instruction Test (RIT) generator.…”
Section: Verified Checker and Resultsmentioning
confidence: 99%
“…The VSCconflict problem, which is the VSC-read problem augmented with the total write order per-location, however, is in P (and similarly, so is the conflict serializability problem in databases). Similar results have been shown for the corresponding problems for the TSO memory model; VTSO and VTSO-read are NP-complete, while the VTSO-conflict problem can be solved in linear time [8] [11]. The Verifying Memory Coherence (VMC) problem, which is like VSC, but involves only one memory location, is also NP-complete; however, VMCread is in P [4].…”
Section: Related Worksupporting
confidence: 68%
“…Unlike previous work [8][11], our goal in this paper is to develop a sound and complete algorithm (i.e. no false errors reported and no consistency errors left undetected) which is practically applicable.…”
Section: Introductionmentioning
confidence: 99%
“…In the single entry version, the two processes attempt to enter into their critical section only once. Verifying this can be done with our implementation, as well as with other tools, such as those of [6], [5] or [16]. Verification becomes more difficult when considering the repeated entry version.…”
Section: Resultsmentioning
confidence: 99%